Graphics' design work: Hudoq Mask / Dunstan Nanang James - James, Dunstan Nanang (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
The Hudoq mask is an important cultural and spiritual symbol for the Kenyah ethnic community in Sarawak and it symbolizes the diverse cultures in Sarawak. The artwork focuses on the unique characteristics of the Hudoq Mask through the understanding of media dimension. The artwork combines shape, unity, and emphasis as the elements and principles.